Isolation and characterization of Dehydrin promoter region from sugarcane (Saccharum officinarum L.) - Hayati MINARSIH; Sonny SUHANDONO; Anissa K FUADI; Tati KRISTIANTI; Riza A PUTRANTO; Deden SUKMAJDAYA; . SUSTIPRIJATNO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2020)
The development of molecular biology techniques nowadays has enabled to engineer drought tolerant sugarcane by genetic engineering to accelerate the breeding program. Dehydrin (DHN) is known to have an important role in plant response and adaptation to abiotic stresses (drought, high salinity, cold, heat, etc.). While plant tissues are subjected to drought stress (dehydration), DHN protein is accumulated to high content throughout all vegetative or generative tissues. The research aimed to isolate and characterize the DHN promoter from sugarcane that can be used as transformation material in generating drought tolerant sugarcane. Specific primers for DHN promoter amplification were designed and DHN promoter region was successfully isolated by PCR cloning method. Two putative promoter sequences were identified namely Pr-1DHNSo and Pr-2DHNSo. In silicoanalyses were carried out and cis-regulatory elements motifs that play a role in adaptation on abiotic stress as well as biotic stress including ABRE, MBS, CGTCA-motif, TGACG-motif, GARE-motif, P-box TCA-element and Box-W1 were identified. The promoter Pr-1DHNSo was then cloned into pBI121 expression vector by Overlap Extention PCR (OE-PCR) for further characterization. Functional test of the promoter construct pBI- Pr-1DHNSo was conducted through Agrobacterium transformation into sugarcane calli. GUS assay and PCR analysis showed that the DHN promoter was transformed and expressed in the sugarcane calli.